Sense and sensibility - Austen, Jane (J.M. Dent ; E.P. Dutton, 1906)
A wonderfully entertaining tale of flirtation and folly that revolves around two starkly different sisters, Elinor and Marianne Dashwood. While Elinor is thoughtful, considerate, and calm, her younger sister is emotional and wildly romantic. Both are looking for a husband, but neither Elinor's reason nor Marianne's passion can lead them to perfect happiness-as Marianne falls for an unscrupulous rascal and Elinor becomes attached to a man who's already engaged.
A wonderfully entertaining tale of flirtation and folly that revolves around two starkly different sisters, Elinor and Marianne Dashwood. While Elinor is thoughtful, considerate, and calm, her younger sister is emotional and wildly romantic. Both are looking for a husband, but neither Elinor's reason nor Marianne's passion can lead them to perfect happiness-as Marianne falls for an unscrupulous rascal and Elinor becomes attached to a man who's already engaged.
Keywords: Young women. / fast / (OCoLC)fst01183301; Manners and customs. / fast / (OCoLC)fst01007815; Young women / England / Fiction.; England. / fast / (OCoLC)fst01219920; England / Social life and customs / 19th century / Fiction.; Fiction. / fast / (OCoLC)fst01423787